Fixní kombinace a adherence u pacientů po infarktu myokardu nebo s kardiovaskulárním onemocněním - zkušenosti v rámci studie SECURE - Lubanda, Jean-Claude; Lubanda, Hana (Cor et Vasa, 2024)
A lack of adherence is associated with a worse prognosis. Decreasing adherence in post-MI patients leads to an increased risk of recurrence of ischemic events. In addition, due to the aging population and improved quality care for ACS with better survival, there is an increase in the number of patients who need more personalized secondary preventive interventions. For these patients, improving adherence is another way to improve their prognosis. The latest research shows that combination therapy, preferably in a fixed combination, should improve patient adherence and reduce the risk of CV disease complications. Thanks to the reduction in the number of tablets, the patient can stay on therapy for a longer period, because it is easier than using several tablets at once. The use of fixed combinations therapy in patients after MI as soon as possible, ideally already at discharge, leads to a significant improvement in adherence and a reduction in the risk of recurrence of ischemic events and a reduction in cardiovascular death, as demonstrated by the SECURE study. We should be able to ensure maximum patient adherence to treatment by administering fixed combinations of drugs with a proven efficacy especially an improvement of cardiovascular outcome.
Keywords: Atorvastatin; fixní kombinace léků; Aspirin; lidé; klinická studie jako téma; ramipril; Clinical Studies as Topic; Medication Adherence; adherence k farmakoterapii; sekundární prevence; Secondary Prevention; Ramipril; Cardiovascular Diseases; atorvastatin; Myocardial Infarction; kardiovaskulární nemoci; Drug Combinations; infarkt myokardu; Humans